Clinico-pathological evaluation of oral melanotic macule, oral pigmented nevus and oral mucosal melanoma - Buery, R.R.; Siar, C.H.; Katase, N.; Fujii, M.; Liu, H.; Kubota, M.; Tamamura, R.; Tsujigiwa, H.; Nagatsuka, H. (Journal of Hard Tissue Biology, 2010)
Focal pigmented melanocytic lesions rarely occur in the oral cavity but should not be taken for granted for they may represent markers or risks for oral mucosal melanoma (OMM). The study investigated the clinical and pathological features of focal pigmented lesions of melanocytic origin focusing on oral melanotic macule (oral MM), oral pigmented nevus (OPN) and OMM. Immunohistochemistry was employed with S100, HMB-45, Melan A, c-kit and Ki-67. Oral MM mostly occurred on the gingiva and buccal mucosa while OPN mostly occurred on the buccal mucosa. OMM occurred on the palate and gingiva. A female gender predilection was observed in oral MM. Most of the benign lesions were less than 6 mm in diameter while OMM had greater than 10 mm in diameter. Benign lesions occurred in almost the same location as that of OMM. S100 and c-kit were detected in most benign cases while HMB-45 and Melan A were focally detected in some cases. S100, HMB-45 and Melan A expressions were detected in all cases of OMM. Ki-67 was only detected at the epithelial basal layer in oral MM and was completely negative in nevus cells. In OMM, Ki-67 was more than 80. In conclusion, oral MM and OPN may not be markers of risk for OMM but excisional biopsy is highly recommended for clinically undefined lesions greater than 6 mm in diameter. The combination of S100, c-kit, HMB-45 and Melan A can be utilized to support the diagnosis of OMM. Â© 2010 The Hard Tissue Biology Network Association Printed in Japan.